A Clinical Study Evaluating Changes in the Microbial Flora Around Dental Implants During Various Stages of Implant Restoration. Issue 5 (October 2015) - Herekar, Manisha; Sethi, Megha; Prithviraj, Doddammane R.; Bhat, Kishore; Fernandes, Aquaviva; Patil, Viraj
Abstract : Purpose: This study evaluated the microbial colonization of dental implants in healthy patients before placing the implants and during the various stages of implant treatment. Materials and Methods: Saliva (in completely edentulous patients) and gingival crevicular fluid samples (in partially edentulous patients) were collected from patients and analyzed to estimate the growth of microorganisms after culture. Samples were collected during 10 phases of implant placement and prosthesis insertion. Sixty dental implants, 18 of NobelReplace Select (Nobel Biocare) and 42 of GSIII/TSIII (Osstem), were evaluated. The microbial titer was estimated in colony-forming units (CFU) per milliliter. The percentage distribution of the organisms during the various phases was noted and the average was compared. Results: Most prevalent microorganism found was gram-positive Streptococci (3.59 × 10 5 CFU/mL). The titer of Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia, and Pseudomonas being 0.42 × 10 5 CFU/ml, 0.15 × 10 5 CFU/mL, 0.09 × 10 5 CFU/mL, and 0.03 × 10 5 CFU/mL, respectively. The titer of these organisms noted during the experimental phase was low. A similarity was observed in the maximum colony-forming unit per milliliter between baseline and completion of implant therapy indicating establishment of equilibrium. Conclusion: Regular microbial evaluation along with clinical and radiographic monitoring could help in recognizing the potential for periimplantitis and in prevention of the same.